Evaluasi Dampak Program: Studi Kasus Program Keluarga Harapan (PKH) di Kabupaten Enrekang - Sulfadli, Sulfadli; Susanti, Gita; Abdullah, Muh. Tang; Pauzi, Rizal (Development Policy and Management Review (DPMR), 2023)
This study aims to describe and explain the impact of the Hope Family Program (PKH) in Alla Sub-district, Enrekang Regency. This research is a descriptive research with a qualitative approach. Data collection techniques used are interviews, observations and documents related to the problem being examined. This study uses the theory of change approach according to Rogers (2014) which includes 5 indicators, namely inputs, activities, outputs, results, and impacts. This research shows that the implementation of the Hope Family Program in Alla Sub-district, Enrekang Regency has an impact on increasing the welfare of poor families in the village. However, the program in this study location has not succeeded in implementing an effective self-graduation stage.